Pengaruh Pembelajaran Berdiferensiasi Berbantuan Booklet terhadap Kemampuan Literasi Dasar dan Motivasi Belajar Siswa Kelas II SD Unggulan Hamzanwadi Tahun Ajaran 2024/2025 - Algae, Risqi Arilia; Haritani, Hartini; Ali, Muhammad (Educatio, 2024)
The objective of this research is to examine the simultaneous impact of differentiated instruction supported by booklets on foundational literacy and student motivation at SDU Hamzanwadi Selong. Foundational literacy and differentiated instruction are integral to the Merdeka Curriculum, launched in 2021 by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) through various initiatives, including the "Sekolah Penggerak" (Driving School) program. Differentiated instruction can be further supported by instructional materials, such as booklets. At SD Unggulan Hamzanwadi, literacy skills have not yet been clearly assessed, making it challenging to classify students into levels for differentiated instruction. Furthermore, student motivation remains relatively low in several primary schools in East Lombok. This study employs a one-way MANOVA design, involving two groups: an experimental group and a control group. The experimental group received instruction via differentiated learning with booklet assistance, while the control group followed a conventional instructional model. Data on students’ foundational literacy and learning motivation were gathered through post-tests and observational measures. Results from normality and homogeneity tests indicate that the data is homogeneous and normally distributed. The results of the MANOVA analysis, presented in the Multivariate Tests table, reveal that the use of booklets in differentiated instruction has a significant effect on enhancing foundational literacy and learning motivation, with a significance level of below 0.05. This study concludes that the implementation of booklet-assisted differentiated instruction has a simultaneous positive impact on both foundational literacy and student motivation, as compared to conventional teaching methods. This suggests that booklet-supported differentiated instruction is highly recommended for educators aiming to improve foundational literacy and student motivation.